Model Integratif Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Tradisi dan Inovasi dalam Meningkatkan Kualitas Pembelajaran - Saifuddin Saifuddin (Alpatih Harapan Semesta, 2025)
This research aims to analyze an integrative model in the development of the Islamic Religious Education (PAI) curriculum that combines classical scholarly traditions with modern learning innovations at Dayah Ummul Ayman. The background of this research is based on the need for Islamic educational institutions to maintain traditional values while also responding to the developments of the times. This research uses a qualitative approach with a descriptive method. Data were collected thru observation, interviews, and documentation. The research results show that the implemented integrative curriculum model is capable of improving the quality of learning, both in terms of religious understanding, critical thinking skills, and the formation of students' character. The integration of traditional methods such as bandongan and sorogan with modern approaches like discussions and contextual learning has become the main factor behind this success.